2016
DOI: 10.1016/j.jml.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The independence of syntactic processing in Mandarin: Evidence from structural priming

Abstract: Although it is generally accepted that syntactic information is processed independently of semantic information in languages such as English, there is less agreement about whether the same is true in languages such as Mandarin that have fewer reliable cues to syntactic structure. We report five experiments that used a structural priming paradigm to investigate the independence of syntactic processing in Mandarin. In a recognition memory task, Mandarin native speakers described ditransitive events after repeati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
80
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(95 citation statements)
references
References 51 publications
14
80
1
Order By: Relevance
“…These results are compatible with priming of animacy-function or animacy-order mappings. However, other research has not found priming of animacy to syntactic structure mappings (Bernolet et al 2009;Carminati et al 2008;Huang et al 2016). Bunger et al (2013) and Raffray et al (2014) showed priming of mappings between components of event structures and syntactic structures.…”
Section: Structural Representations and Their Interfacesmentioning
confidence: 72%
See 1 more Smart Citation
“…These results are compatible with priming of animacy-function or animacy-order mappings. However, other research has not found priming of animacy to syntactic structure mappings (Bernolet et al 2009;Carminati et al 2008;Huang et al 2016). Bunger et al (2013) and Raffray et al (2014) showed priming of mappings between components of event structures and syntactic structures.…”
Section: Structural Representations and Their Interfacesmentioning
confidence: 72%
“…Ambridge, González-Márquez et al, Günther, Lester et al, and Ziegler et al express some scepticism about a level of syntactic representation that is independent of semantic and lexical information. The finding that priming of syntactic structure is not enhanced when thematic mappings or semantic features are repeated (Bock & Loebell 1990;Huang et al 2016;Messenger et al (2012b)) suggests that semantic information is not incorporated into syntactic structure. It specifically fits badly with the construction-based approach advocated by Günther, who suggests that priming effects might hold between entire constructions (which could be related but of different types), or just their syntactic (i.e., form) or their semantic (i.e., meaning) components.…”
Section: R10 Details Of Our Theorymentioning
confidence: 99%
“…First, thematic role priming cannot be reduced to animacy. For example, in Chang et al (2003), both post-verbal arguments were inanimate, and thus animacy was equated across the two constructions (see also Bernolet, Hartsuiker, & Pickering, 2009;Carminati, van Gompel, Scheepers, & Arai, 2008;Cho-Reyes et al, 2016;Huang, Pickering, Yang, Wang, & Branigan, 2016;Köhne, Pickering, & Branigan, 2014;Ziegler et al, 2017a). Second, it is also clear that animacy can influence priming (Bock, Loebell, & Morey, 1992;Gámez & Vasilyeva, 2015; for review and discussion, see Branigan, Pickering, & Tanaka, 2008).…”
Section: Structural Priming and Animacymentioning
confidence: 99%
“…Priming also clearly occurs even when animacy cannot be used as a reliable cue to argument order, as is true for the locatives (see also Bernolet et al, 2009;Carminati et al, 2008;Cho-Reyes et al, 2016;Huang et al, 2016;Köhne et al, 2014;Ziegler et al, 2017a). Thus, we expect to find priming in Exp.…”
Section: Experiments 2 and 3: Replicating And Extending Chang Et Al mentioning
confidence: 99%
“…In fact, some may never produce priming (e.g., order of animacy; Bernolet et al, 2009; Huang, Pickering, Yang, Wang, & Branigan, in press; though cf. Bock, Loebell, & Morey, 1992), and others may only lead to priming in the absence of a constituent structure alternation (i.e., constituent structure priming tends to override thematic priming; Bock & Loebell, 1990; Messenger, Branigan, McLean, & Sorace, 2012).…”
Section: Structural Priming From Anomalous Sentencesmentioning
confidence: 99%